PALANQUE DE PAPEL: O DISCURSO POLÍTICO DOS JORNAIS EVANGÉLICOS BRASILEIROS NO PERÍODO DA REPÚBLICA VELHA - Souza, Márcio Pereira de (2007)
Since its origins in the second half of the 19th century, Brazilian Protestantism is characterized by its affinity with the written and spoken word. This research is related to this fact, specifically to the written word as it is found in the journals of the numerous Protestant denominations. The denominational journals are important both as ideology supporters or crashers. This way, this work starts from what is written on political and social issues in the articles and printed texts found in the Brazilian evangelical journals, related to the events that characterized the transition from the monarchical government to the republican one. Thus, the primary sources used here are the Protestant newspapers of the end of 19th and beginning of the 20th century, notedly: Imprensa Evangélica, O Estandarte, O Jornal Batista e o Expositor Cristão, respectively: Presbyterian, Baptist and Methodist. The formulated question can be expressed as follows: To what extent the Protestants, through the discourse printed in their journals, expressed their political position? The theoretical basis adopted here used the concepts of rhetoric acts formulated by Tereza Halliday, applied in the understanding of the missionaries, reverend and church written discourses. According to this theory, the written or spoken words are always used to blame or defend, criticize or praise, explain, propose or justify known realities, this is why we are rhetoric beings, use a language as a means of change or reinforcement of perceptions, feelings, values, positioning and actions. By assuming that the transition from Monarchy to Republic in Brazil caused conflicts, this research intends, though discourse analysis, to realize to what extent the Protestant press addressed what happened then. To that, once the primary sources were chosen, it was made a reading of the texts according to its relevance to the proposed aim. This material was selected, then organized and its discourse analyzed from the stand point of the a priori categories. By analyzing it as a phenomenon related to the field of the Social Sciences, we studied the Protestants written discourse, supporting ideologies, imaginative aspects as well as the way they represented the Brazilian and evangelical societies.(AU)